A biallelic mutation links MYORG to autosomal-recessive primary familial brain calcification: letter to the editor - Forouhideh, Yalda; Müller, Kathrin; Ruf, Wolfgang; Assi, Muhannad; Şeker, Tuncay; Tunca, Ceren; Knehr, Antje; Strom, Tim M; Gorges, Martin; Schradt, Falk; Meitinger, Thomas; Ludolph, Albert C.; et al. (Brain, 2019)
Sir,Primary familial brain calcification (PFBC) is an adult-onset hereditary disease marked by calcium deposits in multiple parts of the brain and progressive symptoms that can include cerebellar and extrapyramidal syndromes, dysarthria and neuropsychiatric alterations (Fahr’s syndrome) (Fahr, 1931; Nicolas et al., 2013a, b). Heterozygous mutations in PDGFB, PDGFRB, XPR1 and SCL20A2 can cause autosomal-dominantly inherited PFBC (Wang et al., 2012; Keller et al., 2013; Nicolas et al., 2013a, b; Legati et al., 2015), while autosomal-recessively inherited cases remained genetically unexplained. Most recently, however, Yao et al. (2018) have suggested that biallelic mutations in the gene KIAA1161/MYORG are a recessive cause for PFBC, based on the analysis of six Chinese families. However, an independent confirmation is currently missing and no MYORG-linked PFBC case has been reported from outside China. Here, we show complementary data indicating that MYORG is a novel PFBC disease gene and provide an in-depth phenotype characterization.
Gesehen am 17.06.2021